Improving Sitting Resistance Through Giving Rewards to Autism Students - Yolanda Ismudar; Damri Damri (Department of Special Education, 2020)
This study aims to analyze the giving of rewording in the form of stickers with star images, in increasing the sitting resistance of autistic students during the learning process. This study used an experimental method with a single-subject research approach. The subjects of this study were sixth-grade autistic students. Researchers made observations during seventeen meetings, all observation data, interviews, and action tests were presented in graphical form. To measure sitting resistance, researchers used a stopwatch analysis tool. The total results of the research on the initial conditions for the five meetings were 2 minutes, 2 minutes, 4 minutes, 3 minutes. Furthermore, in the intervention condition for seven meetings the researcher gave reword in the form of a star sticker image, the results were 4 minutes, 3 minutes, 4 minutes, 6 minutes, 5 minutes, 7 minutes, 8 minutes. At baseline A2 conditions, the results of sitting resistance after being given treatment were 5 minutes, 5 minutes, 6 minutes, 7 minutes, 9 minutes. These results prove that giving rewards in the form of star stickers in the learning process can increase students’ sitting resistance, but it is necessary to develop further research on this issue in different contexts and problems.